City Transport Driver Revenue System with Multiple Linear Regressions in Times of Large-Scale Social Restrictions (Universitas Negeri Semarang, 2020)
Large-scale social restrictions are constraints on residents' activities in an area suspected of being infected with Coronavirus Disease 2019 (COVID-19). This situation happens in Sukabumi Regency area of the regions affected by this enactment. One of the problems caused resulted in city transport drivers' income decreasing by 60% of normal income. This study uses multiple linear regressions because this method can significantly analyze each issue on decreasing city transport driver's income. This study uses primary data, with simple random sampling as the sampling technique. Hypothetical test using F test that the number of passengers, deposits, amount of round trip, gasoline and the number of families affect the amount of income of the city transport driver at the time of large-scale social restrictions. Highly influential variables are round trip amount 2,305 and deposit 6,014.